ENHANCING EMOTIONAL INTELLIGENCE IN HIGHER EDUCATION: THE EFFECTIVENESS OF DOODLING TECHNIQUE - Adhor Aunah Al Hayyi; Weni Kurnia Rahmawati; Nailul Fauziyah (EDUCATIONE, 2025)
The decline of emotional intelligence among Generation Z, as evidenced by recent global and national reports, has underscored the urgent need for innovative interventions in educational settings, especially within Islamic boarding schools (pesantren) where students face intense academic, religious, and social demands. This study aimed to examine the effectiveness of the doodling technique as a counseling intervention to enhance emotional intelligence among mahasantri at Pondok Pesantren Ibnu Katsir 2 Jember. Employing a quantitative quasi-experimental design (Time Series One Group), twelve students identified with low to medium emotional intelligence participated in a structured series of doodling sessions. Emotional intelligence was measured across five domains—self-awareness, self-management, motivation, empathy, and social skills—using a validated questionnaire before and after each intervention cycle. The findings revealed a significant and consistent increase in emotional intelligence scores, with all participants demonstrating measurable improvement as confirmed by the Wilcoxon Signed-Rank Test (p = 0.002). The study concludes that doodling is an effective, accessible, and creative intervention for fostering emotional growth, self-regulation, and resilience among pesantren students. The research not only fills a critical gap by applying the doodling technique in this unique context but also provides empirical support for integrating expressive art strategies into counseling and educational practice. It is recommended that future research involve larger samples, control groups, and longitudinal follow-up to further validate and expand upon these findings.